Method for producing high-purity silicon by comprehensively utilizing aluminum-silicon raw materials through precise gradient cooling and remelting

By employing a precise gradient cooling remelting method for aluminum-silicon raw materials and centrifugal separation technology, the resource utilization problem of low-grade aluminum-silicon raw materials has been solved, enabling the production of high-purity silicon, broadening the sources of industrial silicon raw materials, and solving environmental pollution issues.

CN119430185AInactive Publication Date: 2025-02-14JILIN UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310976702.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-04
Publication Date
2025-02-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing technologies are unable to effectively utilize low-grade silicon-aluminum raw materials to produce high-purity silicon, resulting in resource waste and environmental pollution. Furthermore, the source of raw materials is limited and cannot meet the demand for industrial silicon.

Method used

A precise gradient cooling and remelting method using aluminum-silicon raw materials is employed. By controlling the cooling rate and holding time, an interwoven framework structure of silicon and iron phases is formed. Combined with centrifugation and gravity separation technology, high-purity silicon is extracted.

Benefits of technology

This approach enables the high-value utilization of low-grade silicon-aluminum raw materials, broadens the sources of industrial silicon raw materials, solves the problems of resource waste and environmental pollution, and yields high-purity elemental silicon products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430185A_ABST
    Figure CN119430185A_ABST
Patent Text Reader

Abstract

The invention discloses a method for producing high-purity silicon by comprehensively utilizing an aluminum-silicon raw material for precise gradient cooling and remelting. According to the method, the cooling system is changed, so that the ferro-silicon-aluminum melt obtained after electrothermal reduction of the silicon-aluminum raw material forms a silicon phase and iron phase grain interlaced skeleton structure with controllable size, morphology, phase composition and element composition in the gradient cooling or heat preservation process, and the low-grade silicon-aluminum raw material can be applied to production of high-purity silicon; the raw material source of high-purity silicon is expanded, and the method has important significance for breaking through the limitation of raw materials in silicon industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of smelting technology, and in particular relates to a method for producing high-purity silicon by comprehensively utilizing aluminum-silicon raw materials through precise gradient cooling and remelting. Background Art

[0002] Industrial silicon, also known as quasi-metallic silicon, is mainly used for the production of organic silicon, the preparation of high-purity crystalline silicon materials, and the configuration of silicon-aluminum alloys. Therefore, it is widely used in the production of organic silicon products such as silicone oil, silicone rubber, silicone resin and silane coupling agent, as well as crystalline silicon products used in semiconductor industries such as solar cells and chips, and aluminum-silicon alloy production in the automotive manufacturing industry. At present, the production of industrial silicon is made by smelting silica and carbonaceous reducing agents in a submerged arc furnace, and then casting, cooling, crushing and other steps. Its upstream raw materials are relatively single, the production process is fixed, and the purity of the raw materials is required to be high. Silica is the main raw material for the production of industrial silicon. Therefore, in the face of the current situation where the demand for industrial silicon is growing with the rapid development of modern industry, science and technology, it is of great strategic significance and practical value to seek more universal production processes and broaden the source of raw materials.

[0003] Low-grade silicon-alumina raw materials are natural minerals, industrial waste residues, tailings, etc., with silicon oxide and aluminum oxide as the main components. There are many types in nature, abundant reserves, and low prices, such as low-grade bauxite, kaolinite, clay, kyanite, fly ash, coal gangue, etc. Due to the relatively low aluminum content and high silicon / aluminum ratio, they are not suitable for use as raw materials for the current conventional aluminum industry production, nor can they be used as raw materials for the current industrial silicon production. They can only be used to produce low-value-added products such as ecological bricks, or for landfill treatment, which not only pollutes the environment, but also causes a waste of resources.

[0004] In the prior art, Chinese patent applications CN202011267903.8 and CN202011267925.4 respectively provide a method for preparing aluminum-silicon-iron alloy using high-aluminum coal gangue and grading purification, and a method for preparing aluminum-silicon-iron alloy using high-aluminum fly ash and grading purification. These two methods can obtain aluminum-silicon alloy for casting, aluminum-silicon-iron alloy for deoxidizer, and industrial silicon through graded purification. However, the raw materials used in these two methods are both high in aluminum content, which limits their application.

[0005] In summary, if we can reasonably utilize the silicon and aluminum resources in low-grade silicon-aluminum raw materials and realize the production of high-purity silicon with low-grade silicon-aluminum resources, it will break through the current raw material limitations of silicon industrial production. Summary of the invention

[0006] The technical solution adopted by the present invention to solve the technical problem is:

[0007] A method for producing high-purity silicon by comprehensive utilization of aluminum silicon raw materials through precise gradient cooling and remelting, the steps are:

[0008] (1) crushing the silicon-aluminum raw material and the carbonaceous reducing agent, adding a binder and water to mix them evenly, forming agglomerates, drying to obtain dry agglomerates, and then putting them into an electric arc furnace for reduction reaction to obtain a single-element aluminum-ferrosilicon melt;

[0009] (2) Under controlled cooling conditions, the obtained aluminum-silicon-iron melt is subjected to gradient cooling, wherein the gradient cooling includes the following stages: in the first stage, the temperature is reduced to 800-1300° C. at a cooling rate of 1-20° C. / min and kept at this temperature for 10-200 min; in the second stage, the temperature is reduced to 650-1000° C. at a cooling rate of 0.1-20° C. / min and kept at this temperature for 10-200 min; in the third stage, the temperature is reduced to 600-850° C. at a cooling rate of 0.1-20° C. / min and kept at this temperature for 10-200 min; in the fourth stage, the temperature is reduced to 577-650° C. at a cooling rate of 0.1-20° C. / min and kept at this temperature for 0-200 min; and then the temperature is naturally cooled to room temperature to obtain a silicon-aluminum-iron alloy with a skeleton structure;

[0010] (3) the obtained silicon-aluminum-iron alloy with a skeleton structure is heated to 577-700° C. and centrifuged to achieve solid-liquid separation, wherein the solid state is an interwoven skeleton structure formed by the growth of silicon phase and iron phase;

[0011] (4) crushing and sieving the solid porous interwoven skeleton structure sample composed of silicon phase and iron phase skeleton obtained in the previous step to 40-200 mesh;

[0012] (5) The sieved sample obtained in the previous step is subjected to gravity separation to separate the silicon phase and the iron phase, and the low-density sample is collected as a high-silicon sample;

[0013] (6) The high-silicon sample obtained in the previous step is soaked in 1-5 mol / L hydrochloric acid for 24 hours to obtain elemental silicon with a purity higher than 99.9%, i.e., the high-purity silicon.

[0014] In the above method, the silicon-alumina raw material in step (1) can be selected from high-grade silicon-alumina raw materials, but in the method of the present invention, the silicon-alumina raw material can be selected from low-grade silicon-alumina raw materials, and the Al2O3 content in the low-grade silicon-alumina raw material is not higher than 55%, and the Al / Si (mass ratio) is not higher than 3.

[0015] In the above method, the silicon-alumina raw material in step (1) can be one or a mixture of natural silicon-alumina minerals, solid waste containing silicon-alumina, or artificially synthesized silicon-alumina raw materials, wherein the natural silicon-alumina minerals include bauxite, kaolinite, albite, potassium feldspar, etc., and the solid waste containing silicon-alumina includes bauxite flotation tailings, coal gangue, fly ash, shale slag, etc.

[0016] In the above method, after the silicon-aluminum raw material and the carbonaceous reducing agent in step (1) are added together, the ratio of the three elements of aluminum, silicon and iron is as follows: the aluminum content is 10-88.3wt.%, the silicon content is 11.7-90wt.%, the iron content is 0.01-26.0wt.%, and the iron content is ≤(45.64-0.52Al)wt.% and ≤(40.63-0.41Si)wt.%.

[0017] In the above method, the carbonaceous reducing agent in step (1) includes coal, petroleum coke, calcined anthracite, coke, metallurgical coke, one of which or a mixture of several thereof.

[0018] In the above method, the amount of the carbonaceous reducing agent in step (1) is 90-95% of the required reducing agent. If it exceeds 95%, the metal carbides (especially aluminum carbide) in the alloy will increase, which will not only reduce the alloy yield but also affect the stability of arc furnace smelting.

[0019] In the above method, the mass of the binder added in step (1) is 5-10% of the mixed material, the pelletizing pressure is 50-150 MPa, the pellet drying temperature is 150-200°C, and the moisture content of the pellets after drying is not more than 1%.

[0020] In the above method, the reduction reaction temperature in the electric arc furnace in step (1) is 2200-2500°C.

[0021] In the above method, the interwoven skeleton structure described in step (2) is a skeleton structure constructed by silicon grains and iron phase grains, which still retains the macroscopic structure of the aluminum-silicon-iron alloy described in step (1) to a certain extent in appearance after centrifugal treatment, but is loose and porous inside; the gaps in the skeleton structure are filled with aluminum-silicon alloy similar to a binder.

[0022] In the above method, the silicon phase in the interwoven skeleton structure is mainly composed of silicon element.

[0023] In the above method, the Fe mass content of the iron phase in the interwoven skeleton structure is 9.7-65%, the Al mass content is 10-68%, and the Si mass content is 12-30%.

[0024] In the above method, the physical composition of the iron phase in the interwoven skeleton structure is mainly one or more of Al4FeSi, Al3FeSi2, Al2Fe5Si5, Al9Fe5Si5, and Al3Fe3Si2.

[0025] In the above method, in step (3), the sample is centrifuged for 0 to 360 minutes, the supergravity coefficient is 50 to 500 g, and the separation time is 30 to 360 minutes.

[0026] In the above method, the crushing described in step (4) can be carried out by a hammer crusher, a jaw crusher, a disc crusher, a double-roll crusher, etc., and the mesh size requirement can be achieved through a cyclic crushing method.

[0027] In the above method, the crushing described in step (4) can first be crushed into small pieces with a particle size of 10-20 mm using a hammer crusher, jaw crusher, disc crusher, double-roll crusher, etc., and then the sample can be wet-crushed using a disc crusher, and then wet-sieved using a vibrating screen to obtain a 40-200 mesh sample.

[0028] In the above method, the high-silicon sample described in step (5) refers to a silicon-rich phase with an iron content of less than 0.5% obtained after the self-generated aluminum element in the system is removed by the reduction of the silicon-aluminum raw material.

[0029] In the above method, the re-selection described in step (5) can be separated by a shaking table. The sample after crushing in step (4) is adjusted to a solid-liquid ratio of 1:10 to 1:50, and the slurry is injected into the ore dressing shaking table at a flow rate of 10 to 30 ml / s. The inclination angle of the ore dressing shaking table is set to 5-10°, and the flushing water flow of the ore dressing shaking table is set to 20 to 100 ml / s. A dividing plate is set at the interface between the gray iron phase and the bright silver silicon phase to collect silicon-rich phase samples. The collected high-silicon sample is then injected into the ore dressing shaking table again at a flow rate of 5 to 20 ml / s. The inclination angle of the ore dressing shaking table is set to 3 to 6°, and the flushing water flow of the ore dressing shaking table is set to 20 to 40 ml / s. At this time, the dividing plate is set at the interface between the gray iron phase and the bright silver silicon phase, 5 to 15 mm away from the silicon phase. The high-silicon sample collected again has an iron content of less than 0.5%.

[0030] In the above method, the gravity separation described in step (5) can be carried out by using a cyclone chute to prepare a slurry of about 2-40% of the crushed sample in step (4). After separation, the collected samples with low density are polycrystalline silicon, and the samples with high density are iron-rich phase.

[0031] In the above method, the gravity separation described in step (5) can be separated by a two-product heavy medium cyclone. The solid-liquid ratio of the sample to the heavy medium suspension after screening is 1:2.5-1:4.5, the volume concentration of the heavy medium suspension is 15%-30%, and the heavy medium suspension is composed of one or more of sodium polytungstate, calcium bromide, zinc bromide or calcium iodide. After sorting, the collected low-density sample is polysilicon; the high-density sample is an iron-rich phase.

[0032] The cooling mechanism of the present invention is:

[0033] When the melt is cooled, solidification phases gradually precipitate from the material, and the following steps are performed:

[0034] L→Si

[0035] L→Si+Al3FeSi2

[0036] L+Al3FeSi2→Al4FeSi+Si

[0037] L→Al+Si+Al4FeSi

[0038] First, in the primary crystallization zone of silicon, when the melt begins to cool down, the elemental Si phase will precipitate first as the temperature continues to drop; then, after entering the iron-rich phase zone, Al3FeSi2 also begins to precipitate; when the temperature continues to drop, there will be a melting process, that is, the phase and the remaining liquid phase melt to form Al4FeSi phase and elemental silicon; finally, when the temperature reaches the low eutectic point temperature of the system, the liquid phase will completely solidify and precipitate as elemental aluminum, elemental silicon and Al4FeSi phase.

[0039] According to the ratio of aluminum, silicon and iron elements in the raw materials, the cooling and condensation process is different. In particular, when the melt cooling mechanism is precisely controlled, the grain size of each solidified phase can be effectively controlled, so that the silicon phase and iron-rich phase with larger grain size can be obtained after full growth, which provides the possibility for the effective separation of the subsequent silicon phase and iron phase. At the same time, by adjusting the holding time and cooling rate of each temperature zone, the content ratio of the iron-rich phase Al3FeSi2 and Al4FeSi phase can be effectively adjusted to increase the content of the iron-rich phase Al3FeSi2 in the final solid phase. Due to the obvious difference in the morphology of the iron-rich phase Al3FeSi2 and Al4FeSi grains, the Al3FeSi2 phase is more likely to grow into coarse grains, while the opposite phase Al4FeSi phase tends to grow into fine needles. Needle-shaped grains are very easy to break into smaller particles during the subsequent separation of silicon phase and iron phase, which makes it impossible to separate the two phases through the density difference between the iron phase and the silicon phase, and it is impossible to effectively obtain high value-added single silicon products. However, when the iron-rich phase Al3FeSi2 is dominant in the product, phase separation can be effectively achieved by controlling the large-particle iron-rich phase and silicon phase and utilizing the density difference between the two phases.

[0040] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0041] 1. It provides a new application path for low-grade silicon-aluminum materials, which not only solves the pollution problem of low-grade silicon-aluminum solid waste, but also realizes the high added value utilization of such materials and broadens the raw material sources of industrial silicon and high-purity silicon.

[0042] 2. During the cooling and crystallization process of the aluminum-silicon-iron melt, the silicon phase precipitates and grows at high temperature; as the temperature decreases, the iron phase begins to precipitate and interweaves with the silicon phase to form a unique skeleton structure; as the temperature continues to drop, the remaining aluminum-silicon alloy melt solidifies and exists in the skeleton gaps formed by the silicon phase and the iron phase to form a solid block;

[0043] 3. In the process of forming the interwoven framework of silicon phase and iron phase, the aluminum silicon iron melt is gradually cooled or kept warm by precisely controlling the cooling mechanism, so as to control the size, morphology, phase composition and element composition of the crystal morphology of silicon phase and iron phase and the internal organizational structure of the alloy;

[0044] 4. During the cooling process of the aluminum-silicon-ferrosilicon melt, the silicon phase first precipitates at high temperature. By controlling the cooling rate, insulation temperature and time, the silicon phase gradually grows to a suitable size, which is more conducive to subsequent separation and extraction;

[0045] 5. According to the ratio of aluminum, silicon and iron in the raw materials, a suitable temperature zone is selected for heat preservation or gradient cooling, and suitable heat preservation time and cooling speed are matched to effectively realize the regulation of the phase composition of the iron phase. The precipitated iron phase can be one or more of Al4FeSi, Al3FeSi2, Al2Fe5Si5, Al9Fe5Si5, and Al3Fe3Si2; and through the adjustment of the cooling process, the particle size and growth morphology of the iron phase can be effectively regulated during the transformation of different crystal phases, providing favorable conditions for the subsequent separation of silicon phase and iron phase;

[0046] 6. After strict temperature reduction control, the iron phase can grow into large-sized grains, and effectively improve the previous needle-shaped growth orientation, making it possible to separate silicon and iron. Combined with the density difference between the silicon phase and the iron phase, polysilicon products and iron-rich phase products can be obtained by gravity separation methods such as cyclone troughs and shaking tables. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 Micrograph of the silicon phase and iron phase skeleton structure formed in Example 1.

[0048] Figure 2 This is the EDS analysis result of the iron phase in the skeleton of Example 1.

[0049] Figure 3 This is a photo of the cast aluminum-silicon alloy obtained in Example 1.

[0050] Figure 4 The solids remaining after centrifugation obtained in Example 1 (left) and a partial enlarged photograph (right). DETAILED DESCRIPTION

[0051] The following is a detailed description of an embodiment of the present invention: This embodiment is implemented on the premise of the technical solution of the present invention, and a detailed implementation method and a specific operation process are given, but the protection scope of the present invention is not limited to the following embodiments.

[0052] Example 1

[0053] The gangue and coal crushed to a particle size less than 100 mesh are uniformly mixed in a mass ratio of 1:0.71 to form a mixed material, wherein the mass fraction of Al2O3 in the gangue is 43.78%, the mass fraction of SiO2 is 50.15%, and the mass fraction of Fe2O3 is 1.69%, and the mass fraction of Al2O3 in the coal is 46.01%, the mass fraction of SiO2 is 45.10%, and the mass fraction of Fe2O3 is 4.75%. Then, 6% of the mass of the mixed material is added with a sulfite pulp binder and 10% of water to mix the materials. Then, the mixed materials are made into pellets in a pelletizing machine at a pelletizing pressure of 100MPa, dry and dehydrate the prepared pellets at 120℃ to obtain dry lumps, with the moisture content not exceeding 1%, and then put the dry lumps into an electric arc furnace for reduction reaction, with a smelting temperature of 2200-2500℃. When the molten aluminum silicon iron alloy melt is cooled to 1400℃, it is cast in a mold and placed in a tunnel kiln for gradient temperature control, cooling to 1000℃ at 10℃ / min; keeping at 1000℃ for 30min; cooling to 800℃ at 1.5℃ / min; cooling to 700℃ at 10℃ / min; keeping at 700℃ for 30min; cooling to 580℃ at 2℃ / min. At this time, a skeleton structure composed of large flaky silicon phases and coarse granular iron phases has been formed inside the sample, such as Figure 1 At this time, according to the EDS analysis results, the phase composition of the iron phase in the skeleton is mainly Al3FeSi2 phase, with a small amount of other phases coexisting, and the overall iron phase morphology is coarse-grained, as shown in Figure 2 The melt is further cooled to room temperature to obtain an aluminum-silicon-iron alloy block (such as Figure 3 As shown), the mass fraction of Al is 51.63%, the mass fraction of Si is 43.31%, and the mass fraction of Fe is 5.05%.

[0054] 150kg aluminum-silicon-iron alloy blocks were loaded into a hanging basket, placed in an ultra-gravity centrifugal device equipped with a heating device, heated to 650°C, kept warm for 180 minutes, and the centrifuge was started. The ultra-gravity coefficient was 200g, and the separation time was 180 minutes. The melt was separated by a porous filter plate. After the melt was cooled and solidified, a cast aluminum-silicon alloy (such as Figure 3 As shown) 76.13 kg, of which the Fe mass fraction is 0.87% and the Si mass fraction is 12.78%.

[0055] The solid sample remaining after centrifugation (such as Figure 4As shown), the sample to be separated is crushed by a hammer crusher in a cyclic crushing mode, and 120-200 mesh samples are obtained by screening. The solid-liquid ratio of the crushed material is adjusted to 1:25, and the slurry is injected into the beneficiation shaker at a flow rate of 20ml / s. The inclination of the beneficiation shaker is set to 7°, and the flushing water flow of the beneficiation shaker is set to 50ml / s. A dividing plate is set at the interface between the gray iron phase and the bright silver silicon phase to collect silicon-enriched phase samples. The collected high-silicon sample is then injected into the beneficiation shaker again at a flow rate of 10ml / s. The inclination of the beneficiation shaker is set to 5°, and the flushing water flow of the beneficiation shaker is set to 30ml / s. At this time, the dividing plate is set at the interface between the gray iron phase and the bright silver silicon phase, 10mm away from the silicon phase. The high-silicon sample collected again has an iron content of 0.32%. After the high-silicon sample is soaked in 2mol / L hydrochloric acid for 24 hours, a small amount of impurities such as iron and residual aluminum are washed away to obtain 34.22kg of single-substance silicon product with a purity of 99.5%.

[0056] Example 2

[0057] The gangue and coal crushed to a particle size less than 100 mesh are uniformly mixed in a mass ratio of 1:0.71 to form a mixed material, wherein the mass fraction of Al2O3 in the gangue is 42.96%, the mass fraction of SiO2 is 51.07%, and the mass fraction of Fe2O3 is 1.54%, and the mass fraction of Al2O3 in the coal is 46.01%, the mass fraction of SiO2 is 45.10%, and the mass fraction of Fe2O3 is 4.75%. Then, 6% of the mass of the mixed material is added with a sulfite pulp binder and 10% of water to mix the materials. Then, the mixed materials are made into pellets in a pelletizing machine to make pellets. The pellet pressure is 100MPa. The prepared pellets are dried and dehydrated at 120℃ to obtain dry pellets. The moisture content is required to be no more than 1%. Then the dry pellets are placed in an electric arc furnace for reduction reaction. The smelting temperature is 2200-2500℃. The obtained aluminum silicon iron alloy melt is cast in a mold when the melt is cooled to 1400℃. It is placed in a tunnel kiln for gradient temperature control. The gradient temperature control is carried out, cooling to 900℃ at 10℃ / min; keeping at 900℃ for 30min; cooling to 720℃ at 1.5℃ / min; cooling to 600℃ at 10℃ / min; keeping at 600℃ for 30min. At this time, a skeleton structure composed of large flaky silicon phases and coarse granular iron phases has been formed inside the sample. Naturally cool to room temperature to obtain aluminum silicon iron alloy blocks, in which the mass fraction of Al is 51.05%, the mass fraction of Si is 44.06%, and the mass fraction of Fe is 4.89%.

[0058] 150 kg of aluminum-silicon-iron alloy melt was loaded into a hanging basket and placed in an ultra-gravity centrifuge heated to 650°C. The centrifuge was started with an ultra-gravity coefficient of 200 g and a separation time of 150 min. The melt was separated by a porous filter plate. After the melt was cooled and solidified, 76.13 kg of cast aluminum-silicon alloy that met industrial standards was obtained, in which the Fe mass fraction was 0.87% and the Si mass fraction was 12.78%.

[0059] The solid sample remaining after centrifugation is first crushed into small pieces of 10-20mm by a hammer crusher, and then the sample is wet crushed by a disc crusher, and sieved with a wet vibrating screen to obtain a sample of 120-200 mesh. The solid-liquid ratio of the crushed material is adjusted to 1:25, and the slurry is injected into the mineral processing shaker at a flow rate of 20ml / s. The inclination of the mineral processing shaker is set to 7°, the flushing water flow of the mineral processing shaker is set to 50ml / s, and a dividing plate is set at the interface between the gray iron phase and the bright silver silicon phase to collect silicon-enriched phase samples. The collected high-silicon sample is then injected into the mineral processing shaker again at a flow rate of 10ml / s, the inclination of the mineral processing shaker is set to 5°, and the flushing water flow of the mineral processing shaker is set to 30ml / s. At this time, the dividing plate is set at the interface between the gray iron phase and the bright silver silicon phase, 10mm away from the silicon phase. The high-silicon sample collected again has an iron content of 0.29%. After the high-silicon sample was soaked in 2 mol / L hydrochloric acid for 24 hours and a small amount of impurities such as iron and residual aluminum were washed away, 33.87 kg of elemental silicon product with a purity of 99.8% was obtained.

[0060] Example 3

[0061] The gangue and coal crushed to a particle size less than 100 mesh are uniformly mixed in a mass ratio of 1:0.75 to form a mixed material, wherein the mass fraction of Al2O3 in the gangue is 43.25%, the mass fraction of SiO2 is 47.56%, and the mass fraction of Fe2O3 is 4.45%, and the mass fraction of Al2O3 in the coal is 46.01%, the mass fraction of SiO2 is 45.10%, and the mass fraction of Fe2O3 is 4.75%. Then, 6% of the mass of the mixed material is added with a sulfite pulp binder and 10% of water to mix the mixed material, and then the mixed material is made into a briquette machine. The pellets are formed at a pressure of 100 MPa. The prepared pellets are dried and dehydrated at 120°C to obtain dry lumps, with a water content of no more than 1%. The dry lumps are then placed in an electric arc furnace for reduction reaction at a smelting temperature of 2200-2500°C. When the molten aluminum silicon iron alloy melt is cooled to 1400°C, it is cast in a mold and placed in a tunnel kiln for gradient temperature control, cooling to 950°C at 10°C / min; 950°C for 30min; cooling to 850°C at 1°C / min; 850°C for 30min; cooling to 580°C at 2°C / min. At this time, a skeleton structure composed of large-scale silicon phases and coarse-grained iron phases has been formed inside the sample. At this time, the phase composition of the iron phase in the skeleton is mainly Al3FeSi2 phase, with a small amount of other phases coexisting, and the overall iron phase morphology is coarse-grained. The melt is further cooled to room temperature to obtain an aluminum-silicon-iron alloy block, in which the mass fraction of Al is 50.03%, the mass fraction of Si is 41.94%, and the mass fraction of Fe is 8.03%.

[0062] 150kg of aluminum-silicon-iron alloy blocks were loaded into a hanging basket, placed in an ultra-gravity centrifugal device equipped with a heating device, heated to 600°C, kept warm for 360 minutes, and the centrifuge was started. The ultra-gravity coefficient was 200g, the separation time was 240 minutes, and the melt was separated by a porous filter plate. After the melt was cooled and solidified, 73.13kg of cast aluminum-silicon alloy that met industrial standards was obtained, in which the Fe mass fraction was 0.87% and the Si mass fraction was 12.78%.

[0063] The solid sample left after centrifugation is crushed by a hammer crusher in a cyclic crushing mode, and the sample to be separated is sieved to obtain a sample of 120-200 mesh. The slurry is sorted by a rotary chute, and a slurry of about 10% is prepared. According to the color of the fan-shaped surface formed by the slurry falling in the selection chute, the scraper position is adjusted to collect the slurry with a smaller density (outer circle), which is a high-silicon sample with an iron content of 0.46%. After the high-silicon sample is soaked in 2mol / L hydrochloric acid for 24 hours, a small amount of impurities such as iron and residual aluminum are washed away to obtain 35.46kg of a single silicon product with a purity of 99.0%.

[0064] Example 4

[0065] The gangue and coal crushed to a particle size less than 100 mesh are uniformly mixed in a mass ratio of 1:0.79 to form a mixed material, wherein the mass fraction of Al2O3 in the gangue is 40.35%, the mass fraction of SiO2 is 45.89%, and the mass fraction of Fe2O3 is 8.22%, and the mass fraction of Al2O3 in the coal is 46.01%, the mass fraction of SiO2 is 45.10%, and the mass fraction of Fe2O3 is 4.75%. Then, 6% of the mass of the mixed material is added with sulfite pulp binder and 10% of water to mix the mixed material, and then the mixed material is placed in a briquetting machine. The pellets are made at a pressure of 100MPa. The prepared pellets are dried and dehydrated at 120℃ to obtain dry lumps, with a water content of no more than 1%. The dry lumps are then placed in an electric arc furnace for reduction reaction at a smelting temperature of 2200-2500℃. The obtained aluminum silicon iron alloy melt is cast in a mold when the melt is cooled to 1400℃ and placed in a tunnel kiln for gradient temperature control. The gradient temperature control is performed, cooling to 950℃ at 10℃ / min; cooling to 850℃ at 1℃ / min; cooling to 800℃ at 10℃ / min; and cooling to 580℃ at 2℃ / min. At this time, a skeleton structure composed of large-scale silicon phases and coarse-grained iron phases has been formed inside the sample. At this time, the phase composition of the iron phase in the skeleton is mainly Al3FeSi2 phase, with a small amount of other phases coexisting, and the overall iron phase morphology is coarse-grained. The melt is further cooled to room temperature to obtain an aluminum-silicon-iron alloy block, in which the mass fraction of Al is 47.86%, the mass fraction of Si is 40.11%, and the mass fraction of Fe is 12.13%.

[0066] 150 kg of aluminum-silicon-iron alloy blocks were loaded into a hanging basket, placed in an ultra-gravity centrifugal device equipped with a heating device, heated to 700°C, kept warm for 180 minutes, and the centrifuge was started. The ultra-gravity coefficient was 200 g, the separation time was 120 minutes, and the melt was separated by a porous filter plate. After the melt was cooled and solidified, 73.01 kg of cast aluminum-silicon alloy that met industrial standards was obtained, in which the Fe mass fraction was 0.75% and the Si mass fraction was 11.58%.

[0067] The solid samples remaining after centrifugation are crushed by a hammer crusher in a cyclic crushing mode, and the samples to be separated are screened to obtain samples of 120-200 mesh. The solid-liquid ratio of the crushed material is adjusted to 1:25, and the slurry is injected into the mineral processing shaker at a flow rate of 20ml / s. The inclination of the mineral processing shaker is set to 7°, and the flushing water flow of the mineral processing shaker is set to 50ml / s. A dividing plate is set at the interface between the gray iron phase and the bright silver silicon phase to collect silicon-enriched phase samples. The collected high-silicon samples are then injected into the mineral processing shaker again at a flow rate of 10ml / s. The inclination of the mineral processing shaker is set to 5°, and the flushing water flow of the mineral processing shaker is set to 30ml / s. At this time, the dividing plate is set at the interface between the gray iron phase and the bright silver silicon phase, 10mm away from the silicon phase. The high-silicon sample collected again has an iron content of 0.36%. After the high-silicon sample was soaked in 2 mol / L hydrochloric acid for 24 hours and a small amount of impurities such as iron and residual aluminum were washed away, 34.62 kg of elemental silicon product with a purity of 99.3% was obtained.

[0068] Example 5

[0069] The gangue and coal crushed to a particle size less than 100 mesh are uniformly mixed in a mass ratio of 1:0.80 to form a mixed material, wherein the mass fraction of Al2O3 in the gangue is 41.13%, the mass fraction of SiO2 is 46.25%, and the mass fraction of Fe2O3 is 8.35%, and the mass fraction of Al2O3 in the coal is 46.01%, the mass fraction of SiO2 is 45.10%, and the mass fraction of Fe2O3 is 4.75%. Then, 6% of the mass of the mixed material is added with a sulfite pulp binder and 10% of water to mix the materials. Then, the mixed materials are made into pellets in a pelletizing machine to make pellets. The pressure is 100MPa, the prepared pellets are dried and dehydrated at 120℃ to obtain dry lumps, the moisture content of which is required to be no more than 1%, and then the dry lumps are placed in an electric arc furnace for reduction reaction, the smelting temperature is 2200-2500℃, and the obtained aluminum silicon iron alloy melt is cast in a mold when the melt is cooled to 1400℃, and placed in a tunnel kiln for gradient temperature control, and the gradient temperature control is performed, cooling to 1200℃ at 10℃ / min; cooling to 950℃ at 1℃ / min; cooling to 950℃ at 10℃ / min; keeping at 800℃ for 30min; cooling to 650℃ at 2℃ / min. At this time, a skeleton structure composed of large flaky silicon phases and coarse granular iron phases has been formed inside the sample. The melt is further cooled to room temperature to obtain an aluminum silicon iron alloy block, in which the mass fraction of Al is 48.06%, the mass fraction of Si is 39.97%, and the mass fraction of Fe is 11.97%.

[0070] 150 kg of aluminum-silicon-iron alloy blocks were loaded into a hanging basket, placed in an ultra-gravity centrifugal device equipped with a heating device, heated to 650° C., kept warm for 240 minutes, and the centrifuge was started. The ultra-gravity coefficient was 200 g, the separation time was 180 minutes, and the melt was separated by a porous filter plate. After the melt was cooled and solidified, 77.85 kg of cast aluminum-silicon alloy that met industrial standards was obtained, in which the Fe mass fraction was 1.45% and the Si mass fraction was 14.36%.

[0071] The solid sample remaining after centrifugation is crushed by a hammer crusher in a cyclic crushing mode, and the sample to be separated is sieved to obtain a sample of 120-200 mesh. The solid-liquid ratio of the crushed material is adjusted to 1:25, and the slurry is injected into the mineral processing shaker at a flow rate of 20ml / s. The inclination of the mineral processing shaker is set to 7°, and the flushing water flow of the mineral processing shaker is set to 50ml / s. A dividing plate is set at the interface between the gray iron phase and the bright silver silicon phase to collect silicon-enriched phase samples. The collected high-silicon sample is then injected into the mineral processing shaker again at a flow rate of 10ml / s. The inclination of the mineral processing shaker is set to 5°, and the flushing water flow of the mineral processing shaker is set to 30ml / s. At this time, the dividing plate is set at the interface between the gray iron phase and the bright silver silicon phase, 10mm away from the silicon phase. The high-silicon sample collected again has an iron content of 0.48%. After the high-silicon sample was soaked in 2 mol / L hydrochloric acid for 24 hours and a small amount of impurities such as iron and residual aluminum were washed away, 34.41 kg of elemental silicon product with a purity of 99.2% was obtained.

Claims

1. A method for producing high-purity silicon by comprehensive utilization of aluminum-silicon raw materials through precise gradient cooling and remelting, characterized in that: The steps are: (1) crushing the silicon-aluminum raw material and the carbonaceous reducing agent, adding a binder and water to mix them evenly, forming agglomerates, drying to obtain dry agglomerates, and then putting them into an electric arc furnace for reduction reaction to obtain a single-element aluminum-ferrosilicon melt; (2) Under controlled cooling conditions, the obtained aluminum-silicon-iron melt is subjected to gradient cooling, wherein the gradient cooling includes the following stages: in the first stage, the temperature is reduced to 800-1300° C. at a cooling rate of 1-20° C. / min and kept at this temperature for 10-200 min; in the second stage, the temperature is reduced to 650-1000° C. at a cooling rate of 0.1-20° C. / min and kept at this temperature for 10-200 min; in the third stage, the temperature is reduced to 600-850° C. at a cooling rate of 0.1-20° C. / min and kept at this temperature for 10-200 min; in the fourth stage, the temperature is reduced to 577-650° C. at a cooling rate of 0.1-20° C. / min and kept at this temperature for 0-200 min; and then the temperature is naturally cooled to room temperature to obtain a silicon-aluminum-iron alloy with a skeleton structure; (3) the obtained silicon-aluminum-iron alloy with a skeleton structure is heated to 577-700° C. and centrifuged to achieve solid-liquid separation, wherein the solid state is an interwoven skeleton structure formed by the growth of silicon phase and iron phase; (4) crushing and sieving the solid porous interwoven skeleton structure sample composed of silicon phase and iron phase skeleton obtained in the previous step to 40-200 mesh; (5) The sieved sample obtained in the previous step is subjected to gravity separation to separate the silicon phase and the iron phase, and the low-density sample is collected as a high-silicon sample; (6) The high-silicon sample obtained in the previous step is subjected to acid washing and solid-liquid separation to obtain elemental silicon with a purity higher than 99.9%, i.e., the high-purity silicon.

2. The method according to claim 1, characterized in that The silicoalumina raw material is a low-grade silicoalumina raw material, in which the Al2O3 content is not higher than 55%, and the Al / Si ratio is not higher than 3.

3. The method according to claim 1, characterized in that The silicon-alumina raw material in step (1) is one or a mixture of natural silicon-alumina minerals, solid waste containing silicon-alumina, or artificially synthesized silicon-alumina raw materials, wherein the natural silicon-alumina minerals include bauxite, kaolinite, albite, and potassium feldspar, and the solid waste containing silicon-alumina includes bauxite flotation tailings, coal gangue, fly ash, and shale slag.

4. The method according to claim 1, characterized in that: After the silicon-aluminum raw material and the carbonaceous reducing agent in step (1) are added together, the ratio of aluminum, silicon and iron is as follows: the aluminum content is 10-88.3wt.%, the silicon content is 11.7-90wt.%, the iron content is 0.01-26.0wt.%, and the iron content is ≤(45.64-0.52Al)wt.% and ≤(40.63-0.41Si)wt.%.

5. The method according to claim 1, characterized in that: In the above method, the amount of the carbonaceous reducing agent in step (1) is 90-95% of the required reducing agent amount.

6. The method according to claim 1, characterized in that Step (3) centrifuges the silicon-aluminum-iron alloy with a skeleton structure, keeps warm for 0 to 360 minutes, has a supergravity coefficient of 50 to 500 g, and a separation time of 30 to 360 minutes.

7. The method according to claim 1, characterized in that The gravity separation described in step (5) is carried out by using a shaking table for separation. The sample after crushing in step (4) is adjusted to a solid-liquid ratio of 1:10 to 1:50, and the slurry is injected into the ore dressing shaking table at a flow rate of 10 to 30 ml / s. The inclination angle of the ore dressing shaking table is set to 5-10°, and the flushing water flow of the ore dressing shaking table is set to 20 to 100 ml / s. A dividing plate is set at the interface between the gray iron phase and the bright silver silicon phase to collect silicon-rich phase samples, i.e., high-silicon samples; the collected high-silicon samples are injected into the ore dressing shaking table again at a flow rate of 5 to 20 ml / s, the inclination angle of the ore dressing shaking table is set to 3 to 6°, and the flushing water flow of the ore dressing shaking table is set to 20 to 40 ml / s. At this time, the dividing plate is set at the interface between the gray iron phase and the bright silver silicon phase, 5 to 15 mm away from the silicon phase, and the high-silicon samples are collected again.

8. The method according to claim 1, characterized in that The gravity separation described in step (5) is carried out by using a cyclone chute to prepare a slurry of about 2-40% of the crushed sample in step (4). After separation, the collected samples with low density are polycrystalline silicon, and the samples with high density are iron-rich phase.

9. The method according to claim 1, characterized in that: The gravity separation described in step (5) adopts a two-product heavy medium cyclone for separation. The solid-liquid ratio of the sample to the heavy medium suspension after screening is 1:2.5-1:4.5, the volume concentration of the heavy medium suspension is 15%-30%, and the heavy medium suspension is composed of one or more of sodium polytungstate, calcium bromide, zinc bromide or calcium iodide. After sorting, the collected low-density sample is polycrystalline silicon; the high-density sample is an iron-rich phase.

10. The method according to claim 1, characterized in that The pickling solution in step (6) can be one or more of hydrochloric acid, nitric acid or sulfuric acid, or can be one or more of hydrofluoric acid and hydrochloric acid, nitric acid and sulfuric acid, wherein the concentration of hydrofluoric acid is 0% to 5%, the concentration of the mixed acid solution is 5% to 20%, the solid-liquid ratio is 1:1 to 1:5, the pickling temperature is room temperature to 90°C, the pickling time is 1 to 12h, and the stirring speed is 0 to 300rpm.

Citation Information

Patent Citations

  • Method for preparing aluminum-silicon-iron alloy from high-aluminum coal gangue and conducting graded purification

    CN113913621A

  • A method for preparing aluminum-silicon-iron alloy using high-aluminum fly ash and grading purification

    CN114480855B